A COWORKING SPACE PLANNING WITH AN ERGONOMIC APPROACH (CASE STUDY IN SAMARINDA) - Prayoga, Rizky Wisnu; Arifin, Fitriyani; Sarah, Yuni (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2025)
Technological innovation in the modern era has fundamentally transformed working practices across various sectors. The rise of digitalization and the adoption of hybrid work systems have encouraged a more flexible approach to work, enabling people to operate from virtually anywhere. This Coworking Space design adopts the Design Thinking methodology—an empathetic, user-centered problem-solving approach that emphasizes iterative development. Rather than focusing on identifying problems, the primary objective is to gather concrete data regarding spatial organization and the core functions typically present in Coworking Spaces, particularly within the Samarinda region. The goal is to develop a shared workspace that promotes ergonomics, adaptability, and enhanced user productivity. The central design concept combines Biophilic and Zen Modern principles to cultivate a tranquil atmosphere through the integration of natural elements and a minimalist, balanced aesthetic. The selected materials emphasize both natural and semi-industrial characteristics, including wood, glass, stone, metal grilles, and exposed concrete. Spatial zoning is tailored according to functional needs, encompassing private rooms, both open and enclosed coworking areas, meeting rooms, a mini restaurant, lounge, pantry, and rooftop facilities—providing users with the flexibility to choose work environments that suit their preferences and requirements. This design aspires to serve as a modern, efficient, and adaptable workspace solution that also supports the psychological and physical well-being of its users.